Relationship between endothelial function and skeletal muscle strength in community dwelling elderly women. Issue 6 (6th August 2018) - Yoo, Jun‐Il; Kim, Mi‐Ji; Na, Jae‐Bum; Chun, Yun‐Hong; Park, Young‐Jin; Park, Yongwhi; Hah, Young‐Sool; Ha, Yong‐Chan; Park, Ki Soo
Abstract: Background: The aim of this study is to determine whether there is correlation between endothelial function and skeletal muscle function measured by hand grip strength in elderly women. Methods: This cross‐sectional study used data of NAMGARAM‐2 cohort. The NAMGARAM‐2 cohort consisted of a group of people living in three rural communities. They were enrolled for studies on activity limitation due to age‐related musculoskeletal disorders including knee osteoarthritis, osteoporosis, and sarcopenia. They were residents aged 40 years or older. They agreed to participate in this cohort from March 2016 to May 2017. Peripheral endothelial function was assessed by reactive hyperaemia‐peripheral arterial tonometry using EndoPAT2000 system. Hand grip strength was measured using a digital hand dynamometer. Results: Endothelial function index assessed by EndoPAT was worse in the low grip strength group than that in the normal group of elderly women (1.54 ± 0.51 in the low grip strength group vs. 1.77 ± 0.67 in the normal group, P = 0.003). There was a positive correlation between hand grip strength and endothelial function (r = 0.176, P = 0.007). On stepwise multivariate analysis, endothelial dysfunction (reactive hyperaemia‐peripheral arterial tonometry index < 1.67) significantly increased the risk of low hand grip strength (odds ratio = 2.019; 95% confidence interval = 1.107–3.682; P = 0.022). Conclusions: Endothelial function and skeletal muscle strength had a significant correlation in elderly women, providing additional support for the relevant role of vascular system in sarcopenia.